The Chinese macroeconomy and financial system - Schramm, Ronald M. (Routledge, 2015)
This new textbook on the Chinese economy clearly presents all that the world's second largest economy has accomplished, as well as what work remains to be done. As economic development in China for the last 30 years has been mostly "top down," this text focuses on the macroeconomic and monetary sides of the economy. Utilizing case studies throughout, the book not only uses the traditional macroeconomics tools in explaining the Chinese economy, but also takes a novel approach by assessing China as a company. Through employment of models from finance, such as cash flows and valuations, the text is able to dig deeper into understanding the fundamental characteristics of the Chinese economy. The book also presents extremely useful analysis of the comparison and contrasts between Chinese economic activity and that of the U.S. economy